2008
DOI: 10.1104/pp.108.119222
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Investigation of the Soybean Seed-Filling Proteome and Comparison with a Parallel Study of Rapeseed  

Abstract: To better understand the metabolic processes of seed filling in soybean (Glycine max), two complementary proteomic approaches, two-dimensional gel electrophoresis (2-DGE) and semicontinuous multidimensional protein identification technology (Sec-MudPIT) coupled with liquid chromatography-mass spectrometry, were employed to analyze whole seed proteins at five developmental stages. 2-DGE and Sec-MudPIT analyses collectively identified 478 nonredundant proteins with only 70 proteins common to both datasets. 2-DGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
123
1
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 113 publications
(134 citation statements)
references
References 64 publications
(106 reference statements)
7
123
1
3
Order By: Relevance
“…So far, 746 unique gene accession numbers identified from green and mature seeds constitute the Lotus resource. Similar 2-D gel or Sec-MudPIT-based proteomic studies of seed filling in Medicago and soybean identified 226 and 647 unique proteins, respectively (Gallardo et al, 2003(Gallardo et al, , 2007Hajduch et al, 2005;Agrawal et al, 2008). Comparing these Medicago and soybean proteins against the identified Lotus seed proteins (BLASTP e # 1 3 10 26 ), 39% of the proteins from Lotus were also identified in Medicago, and with soybean the overlap was 60%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, 746 unique gene accession numbers identified from green and mature seeds constitute the Lotus resource. Similar 2-D gel or Sec-MudPIT-based proteomic studies of seed filling in Medicago and soybean identified 226 and 647 unique proteins, respectively (Gallardo et al, 2003(Gallardo et al, , 2007Hajduch et al, 2005;Agrawal et al, 2008). Comparing these Medicago and soybean proteins against the identified Lotus seed proteins (BLASTP e # 1 3 10 26 ), 39% of the proteins from Lotus were also identified in Medicago, and with soybean the overlap was 60%.…”
Section: Discussionmentioning
confidence: 99%
“…Refining the bioinformatics-based comparison presented above, we compiled starch enzyme identifications from the five seed proteomic studies ( Fig. 7; Gallardo et al, 2003Gallardo et al, , 2007Hajduch et al, 2005;Agrawal et al, 2008). Although legume seed starch metabolism may be different from the well-studied processes in leaves and in cereal grains, this approach provided good coverage of known starch biosynthetic and degradation pathways (Fig.…”
Section: Starch Metabolism In Lotus Medicago and Soybeanmentioning
confidence: 99%
“…More recently, techniques of shotgun protein sequencing have developed which, with appropriate informatics support, can provide a much more comprehensive picture of the proteome (Malmstrom et al, 2007). These analyses have established reference maps of the protein complement of developing or mature seed in model and crop species, allowing for the identification of species-specific features (Agrawal et al, 2008;Gallardo et al, 2008). The methods have been applied to total protein extracts, or in some cases to subcellular fractions, as for example in the analysis of nuclear proteins (Repetto et al, 2008).…”
Section: The -Omics Technologies Applied To Legume Seedsmentioning
confidence: 99%
“…For the entire seed, the citations refer to post-genomics experiments carried out in various legume species at the level of the transcriptome (Firnhaber et al, 2005;Buitink et al, 2006;Gallardo et al, 2007;Benedito et al, 2008;Verdier et al, 2008), metabolome (Vigeolas et al, 2008), ionome (Sankaran et al, 2009), and proteome. At the level of the proteome, some citations refer to the mature seed (Watson et al, 2003;Magni et al, 2007;Bourgeois et al, 2009;Krishnan et al, 2009;Natarajan et al, 2009), to the kinetics of seed development (Hajduch et al, 2005;Gallardo et al, 2007;Agrawal et al, 2008;Dam et al, 2009), and to a functional study for identifying targets of thioredoxin (Alkhalfioui et al, 2007). For the separated seed tissues, the citations refer to transcriptome and proteome analyses in soybean (Le et al, 2007) and M. truncatula (Boudet et al, 2006;Zhang et al, 2006;Gallardo et al, 2007).…”
Section: The -Omics Technologies Applied To Legume Seedsmentioning
confidence: 99%
“…A better understanding of the biology and biochemistry of seed development can provide opportunities for the rational engineering of seed content. In this regard, the recent use of transcriptomics and proteomics approaches has begun to provide global views of the compendium of regulatory, structural, and enzymatic proteins involved in carbon assimilation and reserve deposition in the diversity of model and agronomic oilseeds (Ruuska et al, 2004;Hajduch et al, 2005;Katavic et al, 2006;Agrawal et al, 2008;Houston et al, 2009). Although the metabolic pathways involved in seed maturation have been largely predicted using both "omics" (Hajduch et al, 2010) and in vivo labeling approaches (Schwender et al, 2003; for review, see Baud and Lepiniec, 2009), the regulation of the activities in these pathways is only beginning to be discovered.…”
mentioning
confidence: 99%